Renal cell carcinoma with bilateral synchronous adrenal gland metastases: a case report - Koutalellis, Georgios E (Cases Network Ltd, 2009)
INTRODUCTION: Renal cell carcinoma is characterized by its potential of metastasizing widely and to unusual sites, with the metastases occasionally preceding clinical recognition of the primary tumor. Synchronous bilateral adrenal metastases from renal cell carcinoma, without other metastases, are rare and, to our knowledge, only 17 cases have been published in the literature to date. In general, patients with synchronous bilateral adrenal metastases from renal cell carcinoma have a poor prognosis. CASE PRESENTATION: We report a case of right-sided renal cell carcinoma with simultaneous bilateral adrenal metastases in a 58-year-old woman. The primary tumor was localized in the upper and mid pole of the kidney. The diagnosis was established preoperatively by abdominal ultrasound and computed tomography. Surgical treatment consisted of a right radical nephrectomy and bilateral adrenalectomy. Postoperative cortisone acetate replacement was instituted. The pathological findings of the right renal tumor showed clear cell carcinoma and both adrenal tumors showed the same pathology as the right renal tumor. There was no evidence of recurrence after 6 months of follow-up. CONCLUSION: Patients with bilateral synchronous adrenal metastases should be considered to have disseminated metastatic disease. However, good performance status, the presence of paraneoplastic syndrome and the alleviation of refractory pain are important reasons make an urologist to consider radical nephrectomy in renal cell carcinoma patient with metastases.